Conhecimento profissional de professoras de 4º ano centrado no ensino dos números racionais positivos no âmbito do estudo de aula - Utimura, Grace Zaggia (2019)
The theme of positive rational numbers is researched in the early years of elementary school because it presents difficulties for both students and teaching, due to the complexity of this set, because it requires situations that mobilize concepts, relationships, obstacles, different representations and meanings. We consider that interventions and joint work must be carried out for the possible advances in student learning. In this scenario, this qualitative research involved a group formed by seven 4th grade teachers from the São Paulo State Network and the trainer (the researcher herself) who dynamized an extension course that used the "Lesson Study" methodology. The objective of the research portrayed in thesis was to investigate revelations of seven teachers focused on the teaching of positive rational numbers during na extension course that used the teacher training methodology Lesson Study. We sought to answer the following questions: What professional knowledge did the teachers participating in the research reveal in the scope of the Lesson Study methodology when dealing with positive rational numbers? What learning did the teachers participating in the research reveal in the scope of the Lesson Study methodology when dealing with positive rational numbers? We made use logbook; filming and recording of class excerpts; students productions and teachers speeches. The Lesson Study has several characteristics like (i) the collaborative work between teachers and researchers; (ii) teachers choose a theme in the face of the students' difficulties or to teach them; (iii) the class is planned by the group; (iv) a teacher in the group teaches the class that is observed by other teachers, and then the class is reflected by the group. The trainer participated in all these stages of the methodology. Among the results achieved, that the teachers showed signs of curriculum knowledge when working with the material proposed by the network, the EMAI; student knowledge and learning; knowledge of educational practice and some specialized knowledge for teaching, such as equivalence of fractions. But present gaps on the meanings of positive rational numbers in the fractional representation, mainly the ratio.